(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Ganghaka Rasayana (GR) is a much more beneficial drug on wide variety of skin disease such as psoriasis which is difficult to completely cure, but manufacturing procedure is generally tough and time consuming. As per classical references there were 88 numbers of Bhavana (levigation) and according to practical experience it was taken near about six month for completion. Therefore total effort has been spent here to establish and revalidate standard operative procedure for preparation of GR to fulfill objectives of this work. Successfulness of pharmaceutical study can be confirmed through assessing results of analytical study. Analytical study provides idea about quality of finish product and safety profiles the same on the basis of scientific background. Hence without analytical study of the drug, the research which was related to medicinal field is incomplete. Among the main and important aims of conducted analytical study are to assess chemical configuration and the physico chemical changes which occurred after Samskara (procedures) in the finish product. Objectives: To developed standard operative procedure for preparation of GR, to find out the cumbersome in the preparation, reduce time factor in preparation considering with safety and efficacy, find out suitable dispensing form and to analyze the GR for safety and purity. Material and methods: GR was prepared as per Yogaratnakara Rasayanadikara with some modifications and analyze it as per parameters of â€œProtocol of testing ASU medicineâ€ published by Govt. of India Dept. of AYUSH, Ministry of health and family welfare. Physical characters, Physico-chemical analysis, HPTLC, Heavy metals, Microbial load etc parameters were used for analysis of sample of test drug which were prepared by using wet grinder. Results & discussion: Weight of GR after 88 Bhavana was increased accordingly total solid content present in the used liquids for Bhavana. Presence of low amount of moisture content of GR (4.67%) is leading to decrease decomposition and enhance the shelf life and therapeutic value of the same. Low Acid insoluble Ash determines the presence of low adherent dirt as well as sand particles. High % of water & alcohol soluble extractives (62.18% & % 63.12% respectively) confirms the presence of more active principles in the sample. Heavy metal test and Microbial analysis were shown within limit results which refers safety profile of the samples and stability of the drug. Retention factor values in HPTLC confirmed about the multi-polarity index of the compounds and wide range of active principles.